TERRITORIAL FEATURES OF PLACEMENT AND ECONOMICAL USING OF RESOURCE POTENTIAL OF KHARKIV’S REGION - Редин, В. И.; Лаптев, В. Г.; Редина, В. А. (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2013)
In the article considers the resource potential of Kharkiv region and it’s using in branches of the national economy and recreation of people. Analyzes the placement of certain types of resources in Kharkiv’s regions. Their stimulating importance in the development of the economy of the region is shown.